PENGARUH VARIASI SUHU DAN MEDIA PENDINGIN PADA PROSES PACK NITRIDING MATERIAL SUS 630 TERHADAP NILAI KEKERASAN DAN STRUKUR MIKRO - SILALAHI, YOSEPH NETANYAHU; Tamjidilllah, Mastiadi (Universitas Lambung Mangkurat, 2021)
This research investigates the application of material engineering techniques on Stainless steel SUS 630 so that it not only has good resilience and resistance to corrosive properties but also has hard properties on its surface. In an effort to improve the quality of violence on the surface, among others, by surface hardening technique, one of which is a heat treatment technique by adding nitrogen elements to the surface of a material called the nitriding pack process. The nitrogen source in the pack nitriding process comes from urea (CO(NH2)2) with a nitrogen content of 46%. Parameters for controlling this study using variables by applying temperature variations (4200C, 4700C, 5200C, 5700C, 6200C) and cooling media (inside the furnace, room temperature, and with fan) with a holding time of 2 hours. To evaluate this study microstructure testing, diffusion layer testing and micro hardness testing were carried out. From the results of the test it was found that there was no significant transformation of the microstructure shape when comparing with raw material, the optimal value of diffusion layer was in the cooling furnace with a temperature of 6200C with an average of 4.57 μm and white layer 0.53 , the highest hardness was at 6200C with cooling in furnace media which has a value of 80.9 HRN.